Evaluation of Argentine wild sunflower biotypes for drought stress during reproductive stage - Fernández Moroni, Ivana (2012)
As in several regions where sunflower production has moved to areas with limiting water availability, the search for water-stress tolerant genotypes has been intensified. Helianthus annuus ssp. annuus L. constitutes a potential genetic resource because it has naturalized in the semi-arid zone of central Argentina. The assessment of these genetic materials for water deficit tolerance is of interest because they may represent a source of genes for drought tolerance, useful to sunflower breeding. Drought resistant genotypes should be achieved using easily identified phenotypic traits. Parameters like leaf area are widely used to characterize the performance under stress. Leaf temperature is an easily measured physiological parameter that allows an indirect estimate of plant transpiration and is well correlated with water availability. Relative water content indicates the ability to retain water from the soil and expresses plant osmotic adjustment ability. Specific leaf area is a morphological parameter related to leaf thickness. The objectives of this study were to evaluate the drought tolerance of Argentine wild sunflower biotypes and identify morphological and physiological traits expressing differences between stressed biotypes. Wild biotypes were evaluated during three years in the experimental field of the Agronomy Department, Universidad Nacional del Sur, Argentina. Groups of 10-15 plants of each biotype were evaluated under two water conditions, drought (deficit supply) with drip irrigation to cover a half of the potential evapotranspiration during flowering, or with optimal water supply. Soil surface was covered with black polyethylene to exclude rainwater. Wild sunflower comprised five biotypes collected from different habitats in the semiarid region of Argentina. Crosses between the wild biotypes and inbred lines were also included every year. Inbred lines and a commercial hybrid (DK4000) were used as controls. Recorded traits were: plant height, stem diameter, petiole length, leaf area, leaf number, head number and reproductive surface. Leaf parameters were: relative water content (RWC), specific leaf area (SLA), canopy temperature (CT), and chlorophyll content (SPAD). A susceptibility index (SI) was obtained to compare the performance under water stress with that obtained in optimal conditions. Biotype evaluation and parameter characterization were performed separately for each year because water stress levels were different. Wild sunflower responses to water stress were different for all parameters among biotypes, except for plant height and petiole length. Wild biotypes had better RWC and lower SLA than cultivated biotypes. Under water stress wild biotypes showed higher values and greater range of RWC and SPAD than cultivated sunflower. Susceptibility index showed that leaf area of wild sunflower biotypes had lower stress susceptibility than cultivated sunflowers. Nevertheless, wild biotypes showed increased susceptibility to the remaining plant morpho-physiological parameters. RWC and CT had a significant relationship in wild sunflower biotypes under water stress. Drought tolerant type identification was complex because of the complex responses among parameters. Wild biotypes might have a physiological mechanism which allows higher RCA than cultivated sunflower under drought stress. The lower SLA under water deficit could be attributed to a greater leaf thickness and could be related with RCA. Lower leaf area reduction under stress in wild sunflower is an interesting trait that might be used to improve cultivated sunflower. As the RWC is related with CT under stress in wild biotypes, this trait evaluation allows the fast examination of a high number of plants. The assessment of Argentina wild sunflower biotypes for traits associated with drought tolerance has not yet been done. Their identification could increase sunflower crop yield under drought in semiarid regions.